Development and Validation of Learning Material in Statistics and Probability - Molano, Raymund R (ASEAN Journal of Basic and Higher Education, 2020)
This study sought to develop a learning material in Statistics and Probability. It was conducted and involved by Education Program Supervisor in Mathematics, Chief of Curriculum Implementation Division, and Senior High School teachers teaching Mathematics of five mega schools and five non-mega schools of Schools Division Office I Pangasinan. The main instrument of the study was based from the existing learning material used in teaching Statistics and Probability. The data were collated and analyzed using frequency and percentage for profiling, average weighted mean on the computing the levels of data, chi-square for significant relationship where nominal data is involved, and comparing means for significant difference of the data. Based from the findings and results of the study, the researcher concluded that there are existing learning materials used by teachers in teaching Statistics and Probability but are not adequate and relevant. Also, the perception of mega and non-mega schools on the adequacy of the existing learning materials in Statistics and Probability has no difference. Therefore, there is a need to develop learning material to be used in teaching Statistics and Probability learners. The proposed learning material in Statistics and Probability was validated as very acceptable by the Schools Division officials, Mathematics teachers of mega and non-mega schools in SDOI Pangasinan across all criteria.